Global teachers, australian perspectives : goodbye Mr Chips, hello Ms Banerjee - Reid, Carol; Collins, Jock; Singh, Michael (Springer Singapore : Imprint: Springer, 2014)
This is the first book on global teachers and the increasingly important phenomenon of 'brain circulation' in the global teaching profession. A teaching qualification is a passport to an international professional career: the global teacher is found in more and more classrooms around the world today. It is a two-way movement. This book looks at the growing importance of immigrant teachers in western countries today and at teachers who exit from western countries (emigrant teachers) seeking teaching experience in other countries. Drawing on the international literature in Europe, North America, Asia and elsewhere supplemented by rich insights derived from recent Australian research, the book outlines the personal, institutional and structural processes nationally and internationally underlying the increasing global circulation of teachers. It identifies the key drivers of global teacher mobility: a range of factors including family, lifestyle, classroom experience, travel, opportunities for advancement, discipline, linguistic skills, taxation rates, cultural factors and institutional frameworks and policy support. The book is the first detailed contemporary account of the experiences of Australian immigrant and emigrant teachers in the schools and communities where they teach and live. It makes an important and original theoretical and empirical contribution to the contemporary fields of sociology of education and immigration studies.